(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Education empowers minds that will be able to conceive good thoughts and ideas. Education enables students to do the analysis while making life decisions. Life gives various survival challenges for humans. But education guide human to fight with failure and get success in life.Education makes the national development process fast. Education develops good political ideology. The standard of living of its citizens is largely dependent on the level of education the citizens are able to acquire.Everyone deserves to be educated. Education is the first early investment for child development. Similar, for governments and nations, to make their country developed, their first budget allocation has to be on the education infrastructure in schools and colleges.